THE DEVELOPMENT OF ISLAMIC PODCAST AND STREAMING IN DIGITAL AGE - Chillyness, Altruis Bizurai; Salisa, Nikmah Hadiati; Hermawati, Yuli; Tuharea, Filda (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2025)
The development of Islamic podcasts and streaming still has limitations in the study of its evolution, especially in the Indonesian context. This research uses a qualitative approach with the Uses and Gratifications Theory to analyze audience preferences. The results showed that podcasts and streaming offer flexible access and real-time interaction, which increases audience engagement, despite the challenges of content quality, media competition, and the adaptive nature. The implication of the research is to be a strategic reference for preachers or Islamic creators to innovate, audience research, be interactive, and understand content algorithms.